2013
DOI: 10.1371/journal.pone.0054685
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Sport Performance with ACE and ACTN3 Genetic Polymorphisms: A Systematic Review and Meta-Analysis

Abstract: BackgroundGenetic polymorphism is suggested to be associated with human physical performance. The angiotensin I-converting enzyme insertion/deletion (ACE I/D) polymorphism and the α-actinin-3 gene (ACTN3) R577X polymorphism have been most widely studied for such association analysis. However, the findings are frequently heterogeneous. We aim to summarize the associations of ACE I/D and ACTN3 R577X with sport performance by means of meta-analysis.MethodsWe systematically reviewed and quantitatively summarized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
209
4
33

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(255 citation statements)
references
References 37 publications
9
209
4
33
Order By: Relevance
“…(MA et al, 2013) Consideravam se que os elevados níveis de desempenho dos atletas eram resultantes de treinamento e acompanhamento nutricional específicos, elementos estes fundamentais para o desenvolvimento da aptidão dos atletas de elite. Entretanto estes fatores ao decorrer do tempo demonstraram insuficientes para definir um fenótipo de categoria em performance física humana.…”
Section: A Genética E O Alto Desempenho Físicounclassified
See 2 more Smart Citations
“…(MA et al, 2013) Consideravam se que os elevados níveis de desempenho dos atletas eram resultantes de treinamento e acompanhamento nutricional específicos, elementos estes fundamentais para o desenvolvimento da aptidão dos atletas de elite. Entretanto estes fatores ao decorrer do tempo demonstraram insuficientes para definir um fenótipo de categoria em performance física humana.…”
Section: A Genética E O Alto Desempenho Físicounclassified
“…Sendo assim, o parâmetro mais importante observado durante os gestos desportivos é a velocidade com que a potência muscular pode ser executada (MONTENEGRO et al, 2013). O gene ACTN3, influencia a formação de fibras musculares do tipo II, que são agentes da geração de contrações rápidas e fortes (Ma et al, 2013). Ma et al (2013) e Pasqua et al (2011 apontam que o gene ACTN3 codifica a α-actinina-3 em fibras de músculos esqueléticos, uma proteína fundamental para provocar contrações explosivas, extremamente fortes.…”
Section: Actn3: O Gene Dos Atletasunclassified
See 1 more Smart Citation
“…Moreover, despite intensive research, while there is only a little progress in the identification of genes that are locally or widely associated with athletic qualities [33] with the exception of variants in the genes ACTN3 and ACE [19,21,28]. The reason for this is as follows:…”
Section: Regional Aspects Of Sports Medicinementioning
confidence: 99%
“…In a meta-analysis Alfred, et al [27] it is shown that the ACTN3 RR genotype is more common among European athletes speed and power sports than among athletes. In another metaanalysis Ma, et al [28] also found a positive Association between the ACTN3 RR and RX genotypes and athletic status in speed-power kinds of sports, but only in European populations, but not in Asian or African. Some studies have assessed the association between ACTN3 R577X genotype and athletic status in these Asian athletes like fighters, track and field athletes [24,29].…”
mentioning
confidence: 90%